Decay rate of the 2S122 state of singly ionized helium - Hinds,EA; Clendenin,JE; Novick,R (Physical Review A, 1978)
A precise measurement has been made of the lifetime of He+ in the metastable 2S122 state. The result, Γ2S=525±5 sec-1, is consistent with the theory of spontaneous two-photon decay and places an upper limit |δ|<2.4×10-5 on the amplitude of any parity-nonconserving 2P admixture. © 1978 The American Physical Society.